The Implementation of Traditional Game in Enhancing Students’ Motivation - Filandari, Frizka; Sain, Yuliyanah; Nasrullah, Rahmat; Rusli, Tri Indah (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the implementation of traditional games in English learning and their impact on student motivation at SMPN 20 Kendari. A descriptive qualitative method was used with purposive sampling, involving class 7F students as research subjects. Data were collected through interviews and classroom observations, then analyzed through data reduction, data presentation, and conclusion drawing. The results show that the Lengko-Lengko game significantly increases students’ interest, attention, and participation in learning. The classroom becomes more interactive and enjoyable, encouraging teamwork, responsibility, and student confidence in discussions and asking questions. Beyond academic achievement, the game also strengthens character, promotes positive cultural values, and enhances social relationships among students. Lengko-Lengko proves to be an effective and innovative teaching method that can be applied not only in English lessons but also across other subjects to create meaningful and engaging learning experiences.